KALIGRAFI ISLAM DALAM AKTIVITAS BUDAYA - Ade Setiawan (STAI Darul Quran Payakumbuh, 2016)
This article discusses Islamic graphic art. The existence of Islamic graphic art came with the existence of Islam. At the beginning of the stage, it was functioned to record wahyu by using simple media and instruments. The media often used were flat stones, palm leaves, and sterilized leather of animals. Then on the progress of graphic art was developed into graphic letters producing various types of it. It even was designed in flexible spaces generating imaginative artwork. The graphic art was also combined in various ornaments as well as natural paintings. Until now, the art of Islamic graphic art is developed dealing with the progress of culture and the civilization of Islamic society.